e-Learning through Distributed Virtual Environments - Christos Bouras; Thrasivoulos Tsiatsos; A Philopoulos (Journal of Network and Computer Applications, Academic Press, No.3, Vol 24, 2001)
e-learning is one of the emerging needs of the information age. Access to education is going to become crucial for the success of our information society, and therefore a lot of potential is seen in distance learning and distributed virtual environments. The communicative character of the distributed virtual environments would allow students and staff to meet in social shared spaces and engage in on-line real-time seminars and tutorials. Such technologies may mitigate some of the problems of isolation that distance learning brings. This paper presents our work in multi-user distributed virtual environments which are designed and implemented for educational uses in the bounds of the VES project. Furthermore, it presents our proposal for the extensions and reconstruction of the current system in order to create a more efficient system, which can be characterized as a learning virtual environment.